Corporate social responsibility and employee engagement: Role of organizational identification and employees’ lower-order need strength / Osveh Esmaeelinezhad - Osveh , Esmaeelinezhad (2016)
In recent years, a growing number of studies have been carried out regarding the benefits of corporate social responsibility (CSR), while very little attention has been paid to how the perceived external and internal CSR initiatives influence the employees‘positive work-related attitudes with regard to employee engagement. Furthermore, employee engagement is a crucial factor for companies in order to gain sustainable business results. Nevertheless, the percentage of the engaged employees in organizations around the world, especially in Asia is not satisfactory. In spite of the fact that CSR is considered as one of the significant drivers of employee engagement, little is known about the effect of CSR on employees, their attitudes and reactions to, as well as their role in the success of CSR programs in motivating workplace. Besides, most of the studies have been carried out in Western context and the employees‘ attitude toward CSR has been largely remained unexplored in developing countries, including Iran. Furthermore, a few recent studies demonstrated that CSR initiatives may foster organizational identification, but there is a lack of empirical support about the mechanism of the mediation effect of organizational identification between CSR and engagement. In addition, considering that developing countries face dramatic changes in economic and social issues, it can be anticipated that increasing employees‘ deficiency needs play an important role in employees‘ reactions toward company policies. Therefore, probably, if they feel that organization policies are not in line with to meet their deficiency needs, some employees may oppose to CSR initiatives and react with negative behaviours. This study aims to investigate the effect of perceived external and internal CSR on employee engagement by considering the role of employees‘ lower order need strength (LONS) and identification as well as to identify the employees‘ opinion towards CSR programs. This study involves a sample of 1080 employees from four selected organizations in Iran which are pioneers in conducting CSR activities. Structural Equation Modeling (SEM) was used to evaluate the proposed model and testing hypothesis. The analysis of hypothesis supports the positive effect of the perceived external and internal CSR on employee engagement as well as the mediating role of organizational identification and moderating role of employees‘ LONS are proven in the above relationship.Twelve interviews were further conducted to gain a comprehensive understanding in the subject and further knowledge development. This thesis also contributes to the theoretical and practical knowledge, for the first time in providing the evidence on the relationship between perceived external and internal CSR (as a second order construct) and employee engagement. These findings extend the application of the underpinned theories (e.g. social identity theory, social exchange theory and justice theory) in explaining the relationships between CSR, employee engagement, and organizational identification. Practically, this research provides a deeper understanding and further insights for business managers in developing countries provided they consider the strength of employees‘ LONS and identification in determining their CSR policies.